2013
DOI: 10.1177/1082013213497211
|View full text |Cite
|
Sign up to set email alerts
|

Host range and in vitro lysis of Listeria monocytogenes seafood isolates by bacteriophages

Abstract: Listeria-infecting bacteriophages (listeriaphages) can be used to control Listeria monocytogenes in the food industry. However, the sensitivity of many of seafood-borne Listeria strains to phages has not been reported. This research investigated the host ranges of three listeriaphages (FWLLm1, FWLLm3 and FWLLm5) by the formation of lytic zones and plaques on host lawns and in vitro lysis kinetics of listeriaphage FWLLm3. The study also predicted the phage titres required to lyse host cells. The host ranges of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 57 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…Listeria monocytogenes is a gram-positive, facultative anaerobe, and non- sporulating pathogenic bacterium that causes listeriosis. L. monocytogenes is the second foodborne pathogen with the highest mortality rate (around 30%; Arachchi et al., 2014; Goulet et al., 2008). It is well documented that hly and inlA genes are important virulence genes in L. monocytogenes pathogenesis (Lindbäck et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Listeria monocytogenes is a gram-positive, facultative anaerobe, and non- sporulating pathogenic bacterium that causes listeriosis. L. monocytogenes is the second foodborne pathogen with the highest mortality rate (around 30%; Arachchi et al., 2014; Goulet et al., 2008). It is well documented that hly and inlA genes are important virulence genes in L. monocytogenes pathogenesis (Lindbäck et al., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Coagulin C23 is identical to coagulin A, a natural variant of the class IIa bacteriocin pediocin PA1/AcH (Hyronimus et al, 1998). FWLLm1 and FWLLm3 are myoviruses isolated from sheep faeces that infect strains of the species L. monocytogenes as well as other species such as Listeria ivanovii and Listeria welshimeri (Bigot et al, 2011;Arachchi et al, 2013). FWLLm1 was reported to immediately reduce 2.5 log 10 CFU/cm 2 a L. monocytogenes contamination after addition on the surface of vacuum-packed ready-to-eat chicken breast roll (Bigot et al, 2011) suggesting its potential for biocontrol of this pathogen in food.…”
Section: Introductionmentioning
confidence: 99%
“…In the study they achieved 84.5% success in typing with the 100X routine phage test dilution and revealed that the repeatability of the typing was even higher after a few weeks. Arachchi et al (2014) have examined in their study the susceptibility of Listeria species previously isolated from sea products to unexplored bacteriophages. In a total of 50 Listeria strains, 42 strains were shown to be susceptible to phages.…”
Section: Discussionmentioning
confidence: 99%